Host-endophyte-pest interactions of endophytic Fusarium oxysporum antagonistic to Radopholus similis in banana (Musa spp.) - Labuschagne, Nico (University of Pretoria, 2013)
Thesis (PhD (Plant Pathology))--University of Pretoria, 2006.